2009
DOI: 10.1165/rcmb.2008-0073oc
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Fragments/CD44 Mediate Oxidative Stress–Induced MUC5B Up-Regulation in Airway Epithelium

Abstract: Mucus hypersecretion with elevated MUC5B mucin production is a pathologic feature in many airway diseases associated with oxidative stress. In the present work, we evaluated MUC5B expression in airways and in primary cultures of normal human bronchial epithelial (NHBE) cells, as well as the mechanisms involved in its regulation. We found that oxidative stress generated by cigarette smoke or reactive oxygen species (ROS) induces MUC5B up-regulation in airway epithelium from smokers and in NHBE cells, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
61
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 63 publications
6
61
1
Order By: Relevance
“…We have previously reported that ROS induce HA fragmentation (21,23), and that Hyal1, 2, and 3 are expressed in the airway epithelium (26). We and others (26,47) have shown that Hyal2 is selectively increased in inflammatory conditions and that TNF-␣ and IL-1␤ induce Hyal2 gene and protein expression in NHBE cells (26).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…We have previously reported that ROS induce HA fragmentation (21,23), and that Hyal1, 2, and 3 are expressed in the airway epithelium (26). We and others (26,47) have shown that Hyal2 is selectively increased in inflammatory conditions and that TNF-␣ and IL-1␤ induce Hyal2 gene and protein expression in NHBE cells (26).…”
Section: Discussionmentioning
confidence: 89%
“…For instance, GPI-anchored Hyal2 is likely involved in normal HA turnover, where Hyal2 depolymerize HA into ϳ20 kDa (ϳ50 disaccharides units) fragments, delivering them for further lysosomal degradation by Hyal1 (39,50). Soluble Hyal2 could be specifically released by GPI-PLD during inflammation, generating excess HA fragments that overwhelm HA catabolic rates, resulting in the triggering of RHAMM-and CD44-mediated intracellular signaling (22,23). It is reasonable to argue then, that GPI-Hyal2 serves constitutive physiological functions, (39,57,58), while the soluble form actively participates in host defense (22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Furthermore, MUC5AC þ GCH induced by IL-13 in normal HBEC depends on activation of IL-13R-JAK-STAT6 and EGFR-MAPK signaling pathways, as well as NF-kB, 15 relevant in allergic asthma as IL-13 is related to the pathogenesis of this disease. 16 The regulation of MUC5B is less known, but studies using HBEC from smokers and healthy controls showed upregulation induced by oxidative stress from cigarette smoke and reactive oxygen species, 3,17 relevant agents in the etiology of COPD.…”
mentioning
confidence: 99%
“…At least 12 mucins are detected in human lungs, of these MUC5AC and MUC5B are the predominant mucins in normal airways . Airways infection with virus or bacteria, exposure to toxic agents such as cigarette smoke and pollutants that induce airway inflammation and oxidative stress have been shown to upregulate expression of MUC5AC and MUC5B (Borchers et al, 1999;Casalino-Matsuda et al, 2009;Dohrman et al, 1998;Gensch et al, 2004;Haswell et al, 2010;Shao et al, 2004). Cigarette smoke induces expression of number of inflammatory mediators including IL-1 , IL-8, TNF-, MCP-1, leukotrienes through oxidative stress-related pathways from airway epithelial cells, resident macrophages and infiltrated neutrophils, which can increase mucus secretion (Adcock et al, 2011;Choi et al, 2010;Cohen et al, 2009;Mebratu et al, 2011).…”
Section: Mucociliary Clearancementioning
confidence: 99%